Gastric Intussusceptions in a Red Corn Snake (Pantherophis guttatus) Associated with Cryptosporidiosis - Marjorie Bercier; Whitney Zoll; Justin F. Rosenberg; Robson Giglio; Lenice McCoy; William L. Castleman; Matthew D. Johnson; Darryl J. Heard (Case Reports in Veterinary Medicine)
A 3-year-old female red corn snake (Pantherophis guttatus) was presented for a three-week history of anorexia and decreased defecations. On physical examination, a soft midbody intracoelomic swelling was palpated. Transcutaneous coelomic ultrasound revealed a target-like mass on a transverse section of the stomach, suggesting the presence of a gastrointestinal intussusception. On exploratory coeliotomy, a double compounded esophagogastric and gastroduodenal intussusception was diagnosed and reduced surgically. A gastropexy was also performed to prevent recurrence. On histopathology, the gastric glandular mucosa showed moderate to marked proliferation. Diffusely lining the luminal surface of glandular epithelium and free within the lumen were a myriad of protozoa consistent with Cryptosporidium sp. A diagnosis of chronic proliferative gastritis due to Cryptosporidium sp. was made based on these findings. Intussusceptions are rare in reptiles and are infrequently reported in snakes. This is the first report of a double compounded intussusception in a nonmammalian species and the first report of an intussusception involving the stomach in a snake with gastritis due to Cryptosporidium sp.